2020
DOI: 10.21071/az.v69i266.5108
|View full text |Cite
|
Sign up to set email alerts
|

Calidad y fertilidad del semen de conejo diluido con jugo de sandía.

Abstract: Se diseñó un estudio para evaluar la idoneidad del jugo de sandía como diluyente del semen de conejo y la tasa de concepción conejos hembra inseminados. La sandía madura (Citrus lanatus) se obtuvo y procesó en jugo usando el procedimiento estándar. Para el ensayo se usaron un total de 10 conejo macho y 90 conejo hembra , todos de raza New Zealand White x Chinchilla. El semen se recolectó de los conejo macho utilizando una vagina artificial y se diluyó con jugo de sandía a una proporción 1: 0, 1: 0.25, 1: 0.67,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
3
1
0
Order By: Relevance
“…In vivo result showed that watermelon in dextrose saline when used as diluent for rooster semen enhanced fertility and hatchability of eggs than undiluted semen and dextrose saline. This thus corroborates claim by Jimoh & Ayedun [ 13 ] that WMJ is a potent diluent and can be incorporated as extender constituent in the preservation of semen for optimal performance. Finally, watermelon based diluents enhance reproductive output of animals in assisted reproductive techniques which is in line with report of Mangiagalli et al [ 25 ] that lycopene addition affects reproductive performance of multiparous rabbit does inseminated with fresh semen.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In vivo result showed that watermelon in dextrose saline when used as diluent for rooster semen enhanced fertility and hatchability of eggs than undiluted semen and dextrose saline. This thus corroborates claim by Jimoh & Ayedun [ 13 ] that WMJ is a potent diluent and can be incorporated as extender constituent in the preservation of semen for optimal performance. Finally, watermelon based diluents enhance reproductive output of animals in assisted reproductive techniques which is in line with report of Mangiagalli et al [ 25 ] that lycopene addition affects reproductive performance of multiparous rabbit does inseminated with fresh semen.…”
Section: Discussionsupporting
confidence: 90%
“…This study elucidated the importance of watermelon in enhancing viability of rooster semen. From in vitro results watermelon in dextrose saline in semen dilution enhanced progressive motility and low non progressive motility, this is in congruent with a recent study that showed WMJ as a potent semen diluent [ 13 ]. Although, Adebisi and Ewuola [ 17 ] documented the potency of dextrose saline as a superior semen diluent in poultry.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations